Targeting reactive oxygen species and fat acid oxidation for the modulation of tumor-associated macrophages: a narrative review - Teng, Yujian; Xu, Licheng; Li, Wenjing; Liu, Pengyan; Tian, Linli; Liu, Ming (Frontiers in Immunology, 2023)
Tumor-associated macrophages (TAMs) are significant immunocytes infiltrating the tumor microenvironment(TME). Recent research has shown that TAMs exhibit diversity in terms of their phenotype, function, time, and spatial distribution, which allows for further classification of TAM subtypes. The metabolic efficiency of fatty acid oxidation (FAO) varies among TAM subtypes. FAO is closely linked to the production of reactive oxygen species (ROS), which play a role in processes such as oxidative stress. Current evidence demonstrates that FAO and ROS can influence TAMs’ recruitment, polarization, and phagocytosis ability either individually or in combination, thereby impacting tumor progression. But the specific mechanisms associated with these relationships still require further investigation. We will review the current status of research on the relationship between TAMs and tumor development from three aspects: ROS and TAMs, FAO and TAMs, and the interconnectedness of FAO, ROS, and TAMs.